The Relationship Between Students’ Difficulties in Translating English-Indonesian Text and Their Critical Thinking Skills - Ananda Kusuma Widiastuti; Riana Eka Budiastuti; Siti Aimah (Proceedings Series on Social Sciences & Humanities, 2024)
Translation is an activity that cannot be separated from language learning. Some students often experience difficulties in translating. This situation makes students need to think critically in translating. This allows students to learn how to apply these abilities in real-life circumstances while also incorporating them into the educational process, where they must reflect, problem-solve, and evaluate. This is why it is important to investigate the need to apply critical thinking in dealing with students' translation difficulties. To differentiate between them, this research aims to determine the relationship between difficulties in translating and students' critical thinking skills, and tries to find something new as a novelty in this research. This research focused on 45 third semester English Literature students at Muhammadiyah Semarang University as the subject of this research, where they had received translation classes since the first semester. This research used a quantitative descriptive method, with the instrument used in this research being a questionnaire. There are two questionnaires in this research, a questionnaire on difficulties in translating and also a questionnaire on students' critical thinking skills. The results show that there was a relationship between difficulties in translating and students' critical thinking skills. The more students experience difficulties in translating, the higher the students' critical thinking skills. Based on the results of the questionnaire, it was found that students had critical thinking skills to face difficulties in translating which were classified into analysis, evaluation, inference, and reasoning.